Global antimony supply risk assessment through the industry chain - Li, Junhui; Xu, Deyi; Zhu, Yongguang (Frontiers in Energy Research, 2022)
Antimony is a kind of critical metal for the energy transition. The antimony industrial chain is distributed in major developed and developing countries around the world. The source of antimony supply risk also exists in all aspects of the industrial chain. In this paper, we propose an ensemble index for supply antimony risk assessment that includes the Herfindahl Hirschman index, global governance index, human development index, global innovation index, and betweenness centrality in complex networks. Meanwhile, seven commodities in the antimony industrial chain are selected for empirical analysis from 2011 to 2019. The results show that countries with high supply risks of the industrial chain upstream include Canada, France, Germany, India, Japan, Thailand, and the United Kingdom. And, Australia, India, Japan, Thailand, and Vietnam are with high supply risks in the midstream of the industrial chain. Meanwhile, Canada, India, Japan, and Thailand are with high downstream supply risks. Some big countries, like China, the United States, and Germany, play a core role in different sectors of the industrial chain. International competitive relations among big countries have caused a high supply risk of products related to the antimony industry chain. The supply risk in the antimony industrial chain shows that countries must strengthen industrial division and cooperation to maximize their interests. It is suggested to take country-specific measures to mitigate supply risks, including establishing national inventories of critical materials, overseas investment, strengthening the guidance of industrial policies, and accelerating infrastructure construction.